INICIATIVA DE OCUPACIÓN POR CUENTA PROPIA (IOCP): UNA OPORTUNIDAD PARA EL DESARROLLO ECONÓMICO Y SOCIAL EN MÉXICO - Valeria Denisse Solano Diaz; Louis Valentin Mballa (European Scientific Journal, ESJ, 2013)
This article analyzes Own Account Occupancy Initiative in order to contribute to provide information on new forms of support provided by the Ministry of Labor and Social Welfare in Mexico. This institution displayed Own Account Occupational Initiative as an innovative alternative for sustainable human development. In order to develop this paper, we used a method of analysis relying on the Procedures Manual. The paper presents also some successful evidences of the IOCP where it is assumed that the IOCP has the ability to act as a factor of change in the lives of Mexican society contributing to social and economic development in Mexico.